2019
DOI: 10.4081/gh.2019.809
|View full text |Cite
|
Sign up to set email alerts
|

A geospatial model to determine the spatial cost-efficiency of anticoagulation drug therapy: Patients’ perspective

Abstract: Most atrial fibrillation (AF) patients need anticoagulation management to reduce the risk of thromboembolic events and stroke. Currently, two major drug therapies are available: warfarin and direct oral anticoagulant (DOAC). This study examined the spatial costs of these therapies and derived the least-cost market areas for both therapies in the study area. The concepts of spatial costs and the principles of forming market areas were used as theoretical starting points, and the patients’ travel, time-loss, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Campanella et al [ 40 ] observed that digital healthcare not only partially lead to a higher level of customer satisfaction, but also to better organisational performance of public health companies. Such technology can also enhance care protocols and decrease the number of visits to healthcare facilities, as the part of visits can be replaced by self-monitoring and remote follow-up care [ 41 ] and using algorithms to select drugs that require fewer follow-up visits to laboratories from fringe areas [ 42 , 43 ]. In pre- and postoperative telemedicine consultations services given by Korean physicians to Vietnamese patients, a robot-based system for telemedicine decreased in-person contact, travel and cost [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Campanella et al [ 40 ] observed that digital healthcare not only partially lead to a higher level of customer satisfaction, but also to better organisational performance of public health companies. Such technology can also enhance care protocols and decrease the number of visits to healthcare facilities, as the part of visits can be replaced by self-monitoring and remote follow-up care [ 41 ] and using algorithms to select drugs that require fewer follow-up visits to laboratories from fringe areas [ 42 , 43 ]. In pre- and postoperative telemedicine consultations services given by Korean physicians to Vietnamese patients, a robot-based system for telemedicine decreased in-person contact, travel and cost [ 44 ].…”
Section: Discussionmentioning
confidence: 99%